Tubuh Perempuan dalam Nove Jatisaba (2024) Karya Ramayda Akmal: Ambivalensi Tubuh Perempuan dalam Karya Ramayda Akmal Jatisaba - Cinda Amilia Rahman; Aquarini Priyatna; Amaliatun Saleha (ELOQUENCE : Journal of Foreign Language, 2026)
Background: This article examines Ramayda Akmal’s Jatisaba, which portrays the female body as a complex social construct shaped by power relations. Purpose: The aim of this study is to articulate the ambivalence of the female body. Method: The study employs close reading within a narratological framework, drawing on theory of focalization and concept of narrative voice to analyze shifts in the position of the protagonist, as both character and narrator. The analysis focuses on narrative moments that depict embodied experiences, particularly the ambivalence of the female body as it emerges through storytelling strategies. More broadly, the discussion of the female body refers to Beauvoir’s The Second Sex, while the specific issue of bodily ambivalence is addressed through the works of Young and Priyatna. Results and Discussion: The findings indicate that Jatisaba depicts the female body as ambivalent, oscillating between an awareness of its position as the Other and its attempts to negotiate a space of subjectivity within constraining social structures. This ambivalence surfaces through internal focalization and the female narrative voice, which reveal Mae’s capacity to narrate her emotions while simultaneously reinforcing her position as a body that is controlled, objectified, and disciplined by patriarchal institutions. Conclusions and Implications: Jatisaba demonstrates that the ambivalence of the female body arises from the protagonist’s internal conflicts, social pressures, and patriarchal structures. The study’s implication is to open further exploration into the ambivalence of women’s bodies within the broader landscape of Indonesian literature.